Pengaruh Tekanan Stakeholder terhadap Transparansi Laporan Keberlanjutan - Derdjo Djony Saputro; Sonivia Gunawan; Zulkarnain Zulkarnain (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2022)
This study aims to examine the effect of stakeholder pressure on the transparency of sustainability reports. This study uses secondary data in the form of corporate sustainability reports contained in GRI for the 2016-2020 period. Based on the purposive sampling method, this study used 52 companies as samples. The independent variables in this study are stakeholder pressure from environmentally sensitive industries, industries close to consumers, investor-oriented industries and employee-oriented industries which are measured using a dummy variable. The dependent variable in this study is the transparency of the sustainability report, which was obtained using principal component analysis based on four factors, namely reporting frequency, application level, level statement, and assurance of sustainability report. The results show that the influence of stakeholder pressure on environmentally sensitive industries and employee-oriented industries has a negative effect on the transparency of sustainability reports. The pressure of industrial stakeholders close to consumers has a positive effect on the transparency of sustainability reports, while the pressure of investors-oriented industrial stakeholders has no effect on the transparency of sustainability reports.